2020
DOI: 10.3390/su12229656
|View full text |Cite
|
Sign up to set email alerts
|

Creating Realistic Mathematics Tasks Involving Authenticity, Cognitive Domains, and Openness Characteristics: A Study with Pre-Service Teachers

Abstract: Creating mathematics tasks provide opportunities for students to develop their thinking, reasoning, communication, and creativity. This paper presents a study on teaching pre-service teachers to create realistic mathematics tasks in real contexts and amending them through an iterative process of analysis and refinement. The study was undertaken with pre-service teachers from two university training courses in Spain, undergraduate students from a primary teacher training course, and graduate students from an ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Different types of tasks can be approached in mathematics classrooms. In order to acquire adequate mathematical competence, students should develop skills, learn different types of mathematical contents with a variety of complexity levels [45], and use different types of mathematical tasks [46]. Among these types of tasks are mathematics problems, which may be of a routine or a nonroutine nature.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of tasks can be approached in mathematics classrooms. In order to acquire adequate mathematical competence, students should develop skills, learn different types of mathematical contents with a variety of complexity levels [45], and use different types of mathematical tasks [46]. Among these types of tasks are mathematics problems, which may be of a routine or a nonroutine nature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the more aspects that are verified, the more legitimate the lesson is, deepening the knowledge of the SDG. Thereby, the legitimacy of the lessons related to the study of statistics and probability is observed, based on an adaptation of the indicators proposed by Paredes, Cáceres, Diego-Mantecon, Blanco and Chamoso [44]:…”
Section: Categories Analysismentioning
confidence: 99%
“…Following this approach, a task can be considered authentic, believable or fictitious [44]. For a task to be considered plausible or authentic it must develop the indicators described in the 'event', 'question' and 'information' described in the authenticity section of the analysis instrument.…”
Section: Categories Analysismentioning
confidence: 99%
“…Generating opportunities for future teachers to identify the importance of social interaction in learning and promoting a logical and rational understanding of fundamentals may lead to reflective practice [47]. The analysis of the implications that socio-cultural assumptions of learning have on the teaching role can build on professional solutions.…”
Section: Social Interaction As a Learning Principle And Driver Of Changementioning
confidence: 99%
“…The results show that 57.7% of the groups (15 out of 26) did not identify the role of socio-cognitive conflict in learning, while 42.3% of the groups (11 out of 26) identified it. When interacting with environment-related issues, the ability to overcome the conflict it entails is often a significant aspect to be taken into account in order to address said problems [47,68,69].…”
Section: The Role Of Socio-cognitive Conflict In Learning (C3)mentioning
confidence: 99%